Determination of social perception of the role of forest fire break roads and fire lanes in fire prevention - Özer Genç, Çiğdem; Demirci, Kadir Can (Cankiri Karatekin Universitesi, 2025)
Background and Aims As in many countries, forest fires are one of the leading factors that jeopardize the sustainable management of forests in our country. To prevent forest fires, firebreak roads and fire lanes have been established to contain fires early and limit their spread. Therefore, establishing forest fire break roads and fire lanes to protect forests from fire is important in protective, preventive, and fire extinguishing works. Methods This study explores public awareness of the role of firebreak roads and fire lanes in forest fire prevention. It investigates knowledge levels regarding their effectiveness in combating wildfires. The research aligns with the responsibilities in Article 170 of the Constitution, promoting state-public cooperation in forest protection. The study was conducted in the Kastamonu central district and rural neighborhoods of the central district. A literature review was conducted, and survey questions were developed. The number of people to be surveyed was statistically determined as 97 at a 95% confidence level and 10% margin of error using sample size determination methods. The participants' knowledge level about forest roads, forest fire break roads and fire lanes. Their perceptions about the prevention of forest fires by these facilities were determined. Results As a result of the study, it is revealed that people's knowledge about forest fires breaking roads and fire lanes needs to be increased, and awareness should be raised. Conclusions It is essential to know about forest fires, break roads, and fire lanes to act safely, quickly, and effectively in preventing and fighting forest fires.